Evaluating a combined bowel preparation for small-bowel capsule endoscopy: a prospective randomized–controlled study. (19th October 2019) - Hansel, Stephanie L; Murray, Joseph A; Alexander, Jeffrey A; Bruining, David H; Larson, Mark V; Mangan, Thomas F; Dierkhising, Ross A; Almazar, Ann E; Rajan, Elizabeth
Abstract: Background: Capsule endoscopy (CE) is frequently hindered by intra-luminal debris. Our aim was to determine whether a combination bowel preparation would improve small-bowel visualization, diagnostic yield, and the completion rate of CE. Methods: Single-blind, prospective randomized–controlled study of outpatients scheduled for CE. Bowel-preparation subjects ingested 2 L of polyethylene glycol solution the night prior to CE, 5 mL simethicone and 5 mg metoclopramide 20 minutes prior to CE and laid in the right lateral position 30 minutes after swallowing CE. Controls had no solid food after 7 p.m. the night prior to CE and no liquids 4 hours prior to CE. Participants completed a satisfaction survey. Capsule readers completed a small-bowel-visualization assessment. Results: Fifty patients were prospectively enrolled (56% female) with a median age of 54.4 years and 44 completed the study (23 patients in the control group and 21 in the preparation group). There was no significant difference between groups on quartile-based small-bowel visualization (all P > 0.05). There was no significant difference between groups in diagnostic yield ( P = 0.69), mean gastric ( P = 0.10) or small-bowel transit time ( P = 0.89). The small-bowel completion rate was significantly higher in the preparation group (100% vs 78%; P = 0.02). Bowel-preparation subjects reported significantly more discomfort than controls (62% vs 17%; P = 0.01). Conclusions: Combined bowel preparation did not improve small-bowel visualization but did significantly increase patient discomfort. The CE completion rate improved in the preparation group but the diagnostic yield was unaffected. Based on our findings, a bowel preparation prior to CE does not appear to improve CE performance and results in decreased patient satisfaction (ClinicalTrials.gov, No. NCT01243736).